2009
DOI: 10.1080/14926150903047780
|View full text |Cite
|
Sign up to set email alerts
|

Using Video Games in Science Instruction: Pedagogical, Social, and Concept-Related Aspects

Abstract: The potential of using video games to promote learning in classrooms is gaining recognition, but few studies have explored how video games impact teaching and learning in science classrooms. This manuscript reports on the implementation of the video game Nano Legends in four grade 8 science classes in Ontario. Data sources included interviews with teachers and students, classroom observations, online and written student artifacts, and pre and posttests. The findings indicate that the game was effective at comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…The respondents also recognized that the game helped them to build better relationships with other players, as shown by a “very satisfactory” rating (4.49) of item 24. Similar results were obtained in the studies by Jaipal and Figg (2009) and Beylefeld and Struwig (2007) . Finally, respondents agreed that the game is worth recommending (item 25).…”
Section: Resultssupporting
confidence: 91%
“…The respondents also recognized that the game helped them to build better relationships with other players, as shown by a “very satisfactory” rating (4.49) of item 24. Similar results were obtained in the studies by Jaipal and Figg (2009) and Beylefeld and Struwig (2007) . Finally, respondents agreed that the game is worth recommending (item 25).…”
Section: Resultssupporting
confidence: 91%
“…Other researchers varied from this pattern and investigated features of games themselves, and which factors most appealed to players and made video games more effective for their audiences (e.g., Amory, Naicker, Vincent, & Adams, 1999; Salzman, Dede, McGlynn, & Loftin, 1996). Additionally, there was a strong, and currently growing, base of researchers focusing on uses of specific games or computer-based tutorials within schools to teach academic content (Jaipal & Figg, 2009; Simpson & Clem, 2008). These researchers seek to incorporate specific games or to design games that can be used within formal education to teach content within the curriculum, with the hopes that games can better engage students and make teaching more efficient.…”
Section: Research Backgroundmentioning
confidence: 99%
“…For instance, Egenfeldt-Nielsen (2004) found that teachers (a) experienced difficulties in planning instruction with a commercial game to accomplish learning goals, (b) reported inadequate support for students to comprehend a complex game, and (c) reported organizational limitations such as insufficient technical infrastructure. Jaipal and Figg (2009) argued that using games for supporting student learning necessitated teachers to have knowledge about the game to design appropriate curricular activities that connect to game-play. Furthermore, Watson, Mong, and Harris (2011) illustrated how a lack of guidance could lead teachers with game knowledge to lose valuable information about student learning through games, and to create assessments that do not fully combine the strengths of the game with student curricular activities.…”
Section: Game-based Pedagogical Model For Supporting Teachersmentioning
confidence: 99%